2010
DOI: 10.1135/cccc2009548
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and antioxidant properties of rutin

Abstract: The mechanism of electrochemical oxidation of rutin on a glassy carbon electrode was studied at different pH by using several electrochemical techniques (cyclic, linear sweep, differential pulse and square-wave voltammetry) in order to give deeper insight into the mechanism of electrochemical oxidation of rutin and adsorption of its oxidation products on a glassy carbon electrode. It was determined that the rutin oxidation process on a glassy carbon electrode is reversible, pH dependent and includes the transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 39 publications
(57 reference statements)
0
27
0
3
Order By: Relevance
“…Indeed, the electrochemical studies of quercetin and catechin referred anodic potentials at 0.07 and 0.23 V, respectively, at pH 8.0. 17 At the same pH, other authors observed a lower anodic potential of catechin at 0.16 V. 23 On the other hand and as expected, the oxidation peak of quercetin is shifted toward a less positive potential at 0.10 V, raising the pH at 9.0. 27 The second anodic peak is less pronounced and attributed to the oxidation of the paraphenol group of compounds XH6 and XH8 (Fig.…”
mentioning
confidence: 82%
See 1 more Smart Citation
“…Indeed, the electrochemical studies of quercetin and catechin referred anodic potentials at 0.07 and 0.23 V, respectively, at pH 8.0. 17 At the same pH, other authors observed a lower anodic potential of catechin at 0.16 V. 23 On the other hand and as expected, the oxidation peak of quercetin is shifted toward a less positive potential at 0.10 V, raising the pH at 9.0. 27 The second anodic peak is less pronounced and attributed to the oxidation of the paraphenol group of compounds XH6 and XH8 (Fig.…”
mentioning
confidence: 82%
“…4,5 By increasing pH values, the anodic and cathodic peak voltages of hydroxylated xanthones XH2-XH9 decrease, similarly to that reported by other authors for several phenolic compounds. [16][17][18][19] At pH 7.4, compounds XH2 and XH4 (final concentration of 0.05 mM) presented voltammograms with a single irreversible oxidation peak at 0.58 V and 0.64 V, respectively (Scheme 1). The cyclic voltammetric profile of these compounds is similar to that observed in para-substituted flavonoids.…”
Section: Introductionmentioning
confidence: 99%
“…These technologies have been used in several studies as indicators for possible antioxidant activities, both for single compounds and for mixtures [32,33,34,35]. The voltammograms of phenols show one or more peaks.…”
Section: Introductionmentioning
confidence: 99%
“…A concentração de cada amostra necessária para decrescer a concentração inicial de DPPH em 50%, CE 50 [47][48][49][50] o processo no pico I (E paI ) corresponde à oxidação do grupo 3',4'-di-hidroxil no anel B da quercetina, em uma reação envolvendo os prótons. O grupo hidroxila na posição 5-do anel A é oxidado depois e corresponde ao pico II (E paII ), enquanto a reação de oxidação envolvendo o grupo 7-hidroxil não é observada no voltamograma cíclico nas condições utilizadas.…”
Section: Avaliação Da Atividade Antioxidanteunclassified
“…Quanto à reversibilidade das reações que ocorrem nesses processos de oxidação, ainda é contraditória e depende muitas vezes dos parâmetros experimentais empregados. 47,48,50 No voltamograma cíclico do complexo, seguindo as mesmas condições experimentais utilizadas para a quercetina pura, verificam--se os mesmos processos descritos anteriormente, entretanto, com diferenças nos valores dos potenciais. Esses resultados mostraram uma diminuição considerável dos potenciais de oxidação (pico I: 0,305 V vs Fc + /Fc e pico II: 0,565 V vs Fc + /Fc) comparados ao ligante livre, pois a coordenação com o íon metálico faz com que os processos de oxidação ocorram mais facilmente.…”
Section: Avaliação Da Atividade Antioxidanteunclassified